Relationship between Distance Sampling and Carbon Dioxide Emission under Oil Palm Plantation - Ai Dariah; Fahmuddin Agus; Erni Susanti; . Jubaedah (JOURNAL OF TROPICAL SOILS, 2013)
Carbon dioxide emission on peatland under oil palm plantation were highly varied probably due to many factors involved.  The objectives of the research were to evaluate the effect of distance sampling from center of oil palm tree on Carbon dioxide flux, and  to study the factors that cause variability of carbon dioxide flux on peatland under oil palm plantation.  The study was conducted on peatland at Arang-Arang Village, Kumpek Ulu Sub-District, Muaro Jambi District, Jambi Province, on six year old oil palm plantation.  The study was conducted in the form of observational exploratory.  Emission measurements performed on 5 selected oil palm trees at points within 100, 150, 200, 250, 300, 350, and 400 cm from the center of trunk.  Carbon dioxide flux was measured using (IRGA), Li-COR 820.  The results showed that there is significant correlation between the distance of sampling from center of oil palm tree and Carbon dioxide flux.  The farther distance from the tree, Carbon dioxide flux more decreased. Before applying fertilizer, variability of soil fertility was not significantly correlated with the flux of Carbon dioxide, so the difference of Carbon dioxide flux based on distance sampling can be caused by root distribution factor.  After fertilizer application, variability of Carbon dioxide flux under the oil palm tree were beside affected by differences in root distribution, was also greatly influenced by fertilization.Keywords: Carbon dioxide flux, distance sampling, oil palm, peat, root-related respiration [How to Cite: Dariah A, F Agus, E Susanti and Jubaedah. 2013.Relationship between Sampling Distance and Carbon Dioxide Emission under Oil Palm Plantation. J Trop Soils 18 (2): 125-130. Doi: 10.5400/jts.2013.18.2.125][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.2.125] REFERENCESAgus F, E Handayani, van M Noordwijk, K Idris and S Sabiham.  2010 Root respiration interferes with peat CO2 emission measurement. 19th World Congress of Soil Science, Soil Solutions for a Changing World. 1 - 6 August 2010, Brisbane, Australia. Published on DVD.Amador JA and RD Jones.  1993.  Nutrient limitation on microbial respiration in peat soil with diffrent total phosphorus content.  Soil Biol Biochem  25: 793-801.Franklin O, P Hoogberg, A Ekbled and GI Agren.  2003.  Pine forest floor carbon accumulation in response to N and PK addition: Bomb C-14 modeling and respiration studies.  Ecosystem 6: 644-658.  Freeman C, N Ostle and H Kang.  2001.  An Enzymic ‘latch’ on global carbon store-a shortage of oxigen locks up carbon in peatlands by restraining a single enzyme.  Nature 409: 149-149.Hanson PJ, NT Edwards, CT Garten and JA Andrew.  2000.  Separating root and soil microbial contributions to soil respiration: A review of methods and observations.  Biogeochemistry 48: 115-146.Henson IE, and SH Chai.  1997.  Analysis of oil palm productivity.  II. Biomass, distribution, productivity and turnover of the root system.  Elaeis 9: 78-92.Hergoualc’h K and LV Verchot. 2011.  Stocks and fluxes of carbon associated with land use change in Southeast Asian tropical peatlands: A review. Glob Biogeochem Cycl 25. doi:10.1029/2009GB003718.Howarth RW and SG Fisher.  1976.  Carbon, nitrogen, phosporus dynamic during leaf decay in nutrient-enriched stream microecosystems.  Freshwater Biol 6: 221-228.Husen E and F Agus.  2011.  Microbial activities as affected by peat dryness ans ameliorant.  Am J Environ Sci 7: 348-353.Jauhiainen J, A Hooijer and SE Page.  2012.  Carbon dioxide emissions from an Acacia plantation on peatland in Sumatra, Indonesia. Biogeosciences 9: 617–630. DOI:10.5194/bg-9-617-2012.Khalid H, ZZ Zin and JM Anderson.  1999.  Quantification of oil palm biomass and nutrient value in mature planttation.  II Below-ground biomass.  J Oil Palm Res 11: 63-71.Knorr KH, MR Oosterwoud and C Blodau. 2008. Experimental drought alters rates of soil respiration and methanogenesis but not carbon exchange in soil of a temperate fen. Soil Biol Biochem 40: 1781-1791.Law BE, FM Kelliher, DD Baldocchi, PM Anthoni, J. Irvine, D. Moore and SV Tuyl.  2001.  Spatial and temporal variation in respiration in  a young ponderosa pine forest during a summer drought.  Agric Forest Meteorol 110: 27-43.Laiho R, J Laine, CC Trettin and L Finner.  2004.  Scot pine litter decomposition along drainage succession and soil nutrient gradient in peat land forest, and the effect of inter-annual weather variation.  Soil Biol Biochem 36: 1095-1109.Madsen R, L Xu, B Claassen and D McDermit.  2009.  Surface monitoring method for carbon capture and storage projects. Energy Procedia 1: 2161-2168Martoyo K.  1992.  Kajian Sifat Fisik Tanah Podsolik untuk Tanaman Kelapa Sawit (Elaeis gueneensis Jacq) di Sumatera Utara.  Tesis Program Pasca Sarjana,  Universitas Gajah Mada.  Yogyakarta (in Indonesian).Melling L, R Hatano and KJ Goh. 2007. Nitrous oxide emissions from three ecosystem in tropical peatlands of Sarawak, Malaysia. Soil Sci Plant Nutr 53: 792-805.Minkkinen K, J Laine, NJ Shurpali, P Makiranta, J Alm and T Pentilla.  2007.  Heterotropic soil respiration in forestry-drained peatland.  Boreal Environ Res  12: 115-126. Murdiyarso D, K Hergoualc’h K and LV Verchot. 2010 Opportunities for reducing greenhouse gas emissions in tropical peatlands. PNAS 107:  19655-19660.Olsen R, S Linden, R Giesler, and P Hogberg.  2005.  Fertilization of boreal forest reduce of both autrotrophic dan heterotrophic soil respiration .  Glob  Change  Biol  11: 1745-1753.Silvola J, J Valijoki and H Aaltonen.  1985.  Effect of draining and fertilization on soil respiration at three ameliorated peatland site.  Acta For Fem 191: 1-32.Silvola J, J Alm, U Aklholm, H Nykanen and PJ Martikainen.  1996a. Carbon dioxide fluxes from peat in boreal mires under varying temperature and moisture condition.  J Ecol 84: 219-228.Silvola J, J Alm, U. Ahlholm, H Nykanen, and PJ Martikainen.  1996b.  The contribution of plant roots to carbon dioxide fluxes from organic soils.  Biol  Fertil Soils 23: 126-131.Wang W, K Ohseb and J Liuc. 2005.  Contribution of root respiration to soil respiration in a C3/C4 mixed grassland. J Bioscience 30: 507-514.